Comparative analysis of the histopathological and epidemiological profile of ductal and lobular breast carcinomas diagnosed at the Hospital de Clínicas da Universidade Federal do Paraná during the period 2008-2013 - Heloisa Z. Rocha; Graciele C. M. Manica; Lucia de Noronha; Edneia A. S. Ramos; Giseli Klassen
ABSTRACT Introduction: Breast cancer is the second leading cause of cancer death among women worldwide, and epidemiological studies may help understanding its mechanisms. Objective: To carry out a survey of the number of breast cancer cases diagnosed in a period of six years. Methods: The profile of breast cancers diagnosed in a tertiary hospital in Curitiba was compared with the literature, using a retrospective analysis of ductal/special types and lobular breast carcinoma reports issued between 2008 and 2013. Results: Three hundred twenty-seven (91.6%) cases of ductal/special types carcinoma and 30 (8.4%) cases of lobular carcinoma were diagnosed, totaling 357 samples. From these cases, 27 (7.5%) were carcinoma in situ (20 ductal and seven lobular) and 330 (92.4%) were invasive carcinoma (307 invasive ductal/special types and 23 lobular). The prevalence of breast cancer among women was 991% and the majority of patients were older than 50 years of age (67.2%). Regarding the União Internacional de Controle do Câncer/American Joint Committee on Cancer (UICC/AJCC) staging, 49.2% of the ductal/special types tumors were diagnosed in Stages I or II, while 56.6% of lobular carcinomas were diagnosed in Stages II or III/IV. Regarding the Nottingham score, most cases were intermediate grade (43.9%). A total of 61% of the tumors were estrogen receptor positive (ER+) and 54% were progesterone receptor positive (PR+). Moreover, 36.1% presented positive human epidermal growth factor receptor 2 (HER2+), a rate higher than that indicated by the literature. Conclusion: The breast carcinomas evaluated in this study presented a profile similar to that reported in the literature, with some peculiarities inherent to the local pathology service. Nevertheless, the low frequency of in situ cases indicates failure in early diagnosis.